Pengukuran Tingkat Kepuasan Pelanggan Berdasarkan Kualitas Layanan dengan Menggunakan Metode Servqual dan IPA di PT XYZ - Eva Pinata; Andung Jati Nugroho (KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes customer satisfaction and service quality at XYZ Yogyakarta, a local perfume brand facing challenges in maintaining consistent service during peak hours. Utilizing a quantitative approach, the study employs the SERVQUAL method to assess customer satisfaction based on service quality dimensions and Importance-Performance Analysis (IPA) to identify critical areas for improvement. Data was collected from 31 customers via a questionnaire measuring expectations and perceptions using a Likert scale. The SERVQUAL analysis revealed an average perception score of 4.25 against an average expectation score of 3.14, indicating that service quality generally exceeded customer expectations, with all attributes showing a positive gap. The largest gap was observed in “availability of sought-after products” (1.65), while the smallest was “service speed during peak store hours” (0.68). The IPA mapping highlighted “employee speed in assisting with perfume selection” and “service speed during peak store hours” as top improvement priorities (Quadrant I). Essentially, XYZ Yogyakarta largely satisfies its customers, but improving employee assistance with perfume selection and enhancing service efficiency during peak periods are crucial for enhancing customer experience and loyalty.